MITIGATION ON NEGATIVE IMPACTS OF COVID 19 AND COMPLIANCE OF EMPLOYEES TO HEALTH AND SAFETY PROTOCOLS - Herminia B. Gomez; Edna M. Nava; Rev. Fr. Noel G. Gerapusco (Proceeding of the International Conference on Family Business and Entrepreneurship, 2021)
The scariest and most popular virus in the past months is COVID 19. Its threat to life is felt globally. It caused distancing among people, made a person a suspect as host or carrier and effected lockdowns, businesses to crumble, transportation to stop, extreme increase in the usage of internet and social media and loss of lives. Majority had scrambled to shield themselves from the virus and businesses to adapt measures ensuring continuity. The study focused on mitigation of negative impacts of COVID 19 and the compliance of employees to health and safety protocols. The fifty-five employees provided the data gathered through online. Results found that transactions were limited to one (1) employee only, entrance of customers was reduced, time-regulated oral transactions, close contact was avoided and window transactions were encouraged. Likewise, employees complied and protect themselves by wearing masks, washing hands before entering, having face shields worn properly, sanitizing their hands before and after contact with high-touch surfaces, having access to hand hygiene stations and supplies and having facilities for clients to wash. The variables considered in the study age, sex, monthly income and years of employment have no bearing on the mitigation on the impact of COVID 19 and compliance of the employees to health and safety protocols.Keywords: mitigation, safety, protocol, compliance